Study of retention variability on an early growth stage herbaceous plant using a 3D virtual spraying model. (December 2015) - Massinon, Mathieu; Dumont, Benjamin; De Cock, Nicolas; Salah, Sofiene Ouled Taleb; Lebeau, Frédéric
Abstract: A model predicting the spray droplet interception and retention by a single virtual plant has been developed. The model was based on three main experimental inputs: the 3D architecture of a barley plant, the spray quality and the droplet impact behavior. Two contrasted formulation scenarios, limits of the common range covered by pesticide application in terms of surface tension, were tested by changing the droplet behavior at impact in the model. Simulations were undertaken for studying the variability of spray retention resulting from spray quality, applied volume and plant size for a difficult-to-treat target. Results showed that the spray retention efficiency ranged from 6.8% to 96.6% of a theoretical full adhesion scenario, where all intercepted droplets were captured, according to spray quality for the two formulation scenarios tested. Average retention increased with increasing spray fineness, applied volume per hectare and plant size. Variability of deposits, evaluated using the coefficient of variation of simulated retentions, was found to be a function of the mean droplet density according to CV∝N −0.68, where CV is the coefficient of variation and N the number of droplet per square centimeter. Variability was also found to be a function of the plant size according to a relation CV∝S −0.5, where S is the total leaf area of the plant model. The variability of deposits increased with decreasing spray fineness, applied volume per hectare and plant size because of the reduced number of droplets contributing to retention. Wetting properties greatly influenced retention but surprisingly poorly influenced the variability of deposits. Such a modeling approach that is capable of an independent investigation of the influence of various parameters on spray retention can be used to improve understanding of application methods and adjuvants that could help minimizing development of resistance in problematic weed species. Highlights: A virtual model estimated retention by a 3-D herbaceous plant architecture. Two formulation scenarios were studied by changing the droplet behaviors at impact. Retention ranged from 6.8% to 96.6% of full adhesion according to spray quality. Retention variability was found mainly linked to droplet density of the spray. Retention variability was inversely proportional to the plant model scaling factor.